Death to the tsar - Nury, Fabien (Titan Comics, 2018)
"Moscow. September 17th. 1904. In front of the palace of the Governor General of Moscow, the assembled masses protest against widespread poverty. Governor Sergei Alexandrovich is standing on the balcony when he drops his hankerchief-- Inadvertently giving the signal for the soldiers to open fire... The Governor fears for his life and the lives of his family as the repercussions of his deadly mistake resound throughout the whole of Russia... and the assassins close in. Told in two parts, this is the true story of the assassination of Grand Duke Sergei Alexandrovich and a nation on the brink of revolution."--Page [4] of cover.